2021
DOI: 10.3389/fpls.2021.671286
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Sulfatase that Detoxifies Glucosinolates in the Phloem-Feeding Insect Bemisia tabaci and Prefers Indolic Glucosinolates

Abstract: Cruciferous plants in the order Brassicales defend themselves from herbivory using glucosinolates: sulfur-containing pro-toxic metabolites that are activated by hydrolysis to form compounds, such as isothiocyanates, which are toxic to insects and other organisms. Some herbivores are known to circumvent glucosinolate activation with glucosinolate sulfatases (GSSs), enzymes that convert glucosinolates into inactive desulfoglucosinolates. This strategy is a major glucosinolate detoxification pathway in a phloem-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…xylostella, Psylliodes chrysocephala, a specialized insect that feeds on glucosinolate-containing plants, possesses five GSSs, three of which showed weak activity . Although GSS activity is also present in the generalist desert locust (Schistocerca gregaria) and the phloem-feeding whitefly (Bemisia tabaci), the precise numbers of GSSs remain unknown. Sequence analyses showed that both SUMF1a and SUMF1b in P.…”
Section: Discussionmentioning
confidence: 99%
“…xylostella, Psylliodes chrysocephala, a specialized insect that feeds on glucosinolate-containing plants, possesses five GSSs, three of which showed weak activity . Although GSS activity is also present in the generalist desert locust (Schistocerca gregaria) and the phloem-feeding whitefly (Bemisia tabaci), the precise numbers of GSSs remain unknown. Sequence analyses showed that both SUMF1a and SUMF1b in P.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the higher concentration of GLs extracted in our study than that in A. thaliana and other GL-containing feeding experiments, we conclude that the protein expressions of PxGSS1 and PxGSS2 are not influenced by GL concentration, and both are GL-independently expressed. Similarly, the GSS was highly expressed in the B. tabaci whether rearing on GL-rich or GL-free diets ( Manivannan et al 2021 ). Interestingly, another member of PxGSS3 was induced by Trp-GL at both mRNA and protein levels in P. xylostella ( Heidel-Fischer et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gene positions range from 3,168,620 to 3,241,586, showing a high degree of structural complexity. From the similarity of the sulfatase genes between H. armigera and other insects, we speculate that H. armigera sulfatase also detoxifies host plant glucosinolates [41]. The sequence expansion and differences in the H. armigera sulfatase family members may be related to their feeding habits.…”
Section: Discussionmentioning
confidence: 91%
“…Manivannan A and others also measured the expression of the sulfatase gene. In vivo silencing of the B. tabaci GSS gene expression via RNA interference led to lower levels of desulfoglucosinolates in honeydew [41]. The biological function of H. armigera sulfatase requires HaSumf1 to activate and HaSumf1 also has different responses to different concentrations of glucosinolates (Figure 7), which may also be one of the reasons for the different expression of sulfatase.…”
Section: Discussionmentioning
confidence: 99%